Enhancing the cycling stability of a hollow architecture Li-rich cathode via Ce-integrated surface/interface/doping engineering. Issue 2 (8th December 2022) - Yu, Zhaozhe; Yu, Kangzhe; Ji, Fangli; Lu, Quan; Wang, Yuezhen; Cheng, Yan; Li, Huacheng; Xu, Fen; Sun, Lixian; Seifert, Hans J.; Du, Yong; Wang, Jianchuan
Abstract : Hollow architecture and spinel heterogeneous interface strategy provides a novel approach to achieve high-performance cathode materials. Abstract : Li-rich Mn-based cathode materials possess a high specific capacity, but their application is hindered by their inherent anion activity and surface instability. Herein, we propose the design of a spinel heterogeneous interface with oxygen buffering effects in the Li1.2 Mn0.6 Ni0.2 O2 hollow architecture by Ce intervention. The hollow architecture shortens the Li-ion diffusion paths. Ce intervention induces the spinel phase formed on the subsurface, and then constructs a phase boundary to restrain the outward migration of bulk oxygen anions and promote charge transfer. The formed LiCeO2 coating layer with oxygen vacancies accelerates the diffusion of Li ions and decelerates electrolyte corrosion. Moreover, Ce doping in the bulk phase effectually stabilizes the evolution of lattice oxygen and suppresses the structural deformation. The prepared Li1.2 Mn0.6 Ni0.2 Ce x O2− y –LiCeO2 (LLO@Ce–LCO) cathode exhibits a remarkable reversible capacity (267.3 mA h g −1 at 20 mA g −1 ) and great cycling stability (capacity retention of about 86% after 200 cycles at 200 mA g −1 ). This hollow architecture and spinel heterogeneous interface strategy provide a novel approach for achieving high-performance cathode materials.